The Ability of Three Species of Yeast in Inhibiting the in vitro Growth of Sclerotium rolfsii Sacc., the cause of damping off on soybean plants (Glycine max L.) - Hartati, Sri; Setiani, Cahya; Meliansyah, Rika; Yulia, Endah; Mayanti, Tri (CROPSAVER, 2024)
Damping off disease caused by Sclerotium rolfsii is one of the important diseases of soybean plants. Biocontrol is considered as more environmentally friendly control method. Yeast is one of the biocontrol agents that can be used to control plant pathogens. This study was objected to test the potential of three species of yeast in inhibiting the growth of S. rolfsii. The experiment was arranged in the completely randomized design. The treatments were dual culture of the pathogen vs the yeasts on PDA and double dishes of S. rolfsii against three yeast isolates i.e. Rhodotorula minuta Dmg 16 BEP, Candida tropicalis Lm 13 BE, Aureobasidium pullulans Dmg 11 DEP, and a control. The results of the dual culture antagonism test showed that the three tested yeasts could inhibit the colony diameter of S. rolfsii by 23.30% – 40.00%, and the sclerotia formation by 46,33% – 98,05%. The results of the double dishes antagonism test showed that the three tested yeast isolates could inhibit the colony diameter of S. rolfsii by 19.60% – 28.20% and could inhibit 100% of sclerotia formation. The treatment of A. pullulans Dmg 11 DEP produced the highest inhibition in both the dual culture and double dishes antagonism tests.